2021
DOI: 10.1177/0885412221992280
|View full text |Cite
|
Sign up to set email alerts
|

Review of Empirical Studies on Relationship between Street Environment and Crime

Abstract: Creating a safe street environment is the primary goal for urban planners and urban designers. However, the existing research findings on the relationship between street environment and criminal behavior are various and contradictory, which brings confusion to the practice of urban planning and design. This article reviews literature on crime prevention through street environmental design on three spatial levels—street networks, paths, and nodes. This article also explores the causes of diversity and contradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
(99 reference statements)
0
7
0
3
Order By: Relevance
“…According to the CPTED theory, certain environmental features, such as walls and fences, can act as access control measures and inhibit the occurrence of crimes [ 1 , 16 , 17 ]. Better lighting conditions can enhance regional territorial surveillance and deter potential criminals [ 20 , 21 , 22 ]. Green spaces such as trees and grassland can facilitate residents’ outdoor activities and thus promote informal monitoring of the area, thereby retraining the occurrence of crimes [ 1 , 23 , 24 , 25 ].…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the CPTED theory, certain environmental features, such as walls and fences, can act as access control measures and inhibit the occurrence of crimes [ 1 , 16 , 17 ]. Better lighting conditions can enhance regional territorial surveillance and deter potential criminals [ 20 , 21 , 22 ]. Green spaces such as trees and grassland can facilitate residents’ outdoor activities and thus promote informal monitoring of the area, thereby retraining the occurrence of crimes [ 1 , 23 , 24 , 25 ].…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
“…The appearance of street lights [ 18 ] or surveillance cameras [ 19 ] reflects the surveillance level of a territory. A strong sense of territory can increase the probability of criminals being discovered or caught, thus deterring rational offenders [ 20 , 21 , 22 ]. Green elements such as trees and grass can facilitate people’s outdoor activities and thus promote informal monitoring, thereby restraining the occurrence of crimes.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the Highline in New York, 606 in Chicago, and the movement to convert railways to biking/walking trails, such as the Atlanta BeltLine Trail. In a literature review focusing on crime prevention and street characteristics (networks, paths, and nodes), Mao et al (2021) found that street network qualities such as distance, grade, and ambience impact crime. Path activities, visibility, and lighting were critical to deterrence, while nodes that provided the opportunity to escape or had poor visibility were associated with (Mao et al 2021).…”
Section: Vegetated Streets and Urban Greenwaysmentioning
confidence: 99%
“…In response, a large number of scholars have carried out long-term research and practice, and a more complete theoretical system has been formed for the study of the relationship between criminal behavior and spatial environment [34][35][36][37]. In 1961, Jane Jacobs analyzed the security of street space from a sociological perspective [38] and introduced the concept of the "Street Eye", while in 1971, C. Ray Jeffery first developed the first generation of Crime Prevention Through Environmental Design (CPTED) theory [39].…”
Section: Introductionmentioning
confidence: 99%
“…This theory aims to reduce crime opportunities through design means such as enhancing natural surveillance, establishing clear site attributes, and maintaining the image of the spatial environment, and has been widely used in space types such as urban residential areas [42][43][44], green parks [45][46][47][48], greenways [49], urban renewal [50][51][52], tourist attraction sites [53], hospitals [54,55], college towns [56], and public transportation [57]. But only North American countries, represented by the United States and Canada, as well as Korea, Australia, Turkey, and Japan have developed crime prevention guidelines based on it [37] and applied it to educational buildings such as campuses [36,58]. To date, research on the relationship between spatial environment and criminal behavior, as represented by CPTED theory, has never ceased.…”
Section: Introductionmentioning
confidence: 99%